Legalitas Kebijakan Beasiswa Daerah Sebelum Pembentukan Peraturan Daerah: Analisis Hierarki Peraturan Perundang-Undangan di Kabupaten Kotawaringin Barat - Indah Astuti, Sri (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study analyzes the legality and hierarchical synchronization of statutory regulations governing scholarship policy implementation in West Kotawaringin Regency, focusing on the use of a Regent Regulation (Peraturan Bupati) before the enactment of a Regional Regulation (Peraturan Daerah). The issue is examined through the perspectives of the Stufenbaulehre theory and the principle of legality in administrative law. This research employs a normative legal method using statutory and conceptual approaches. Legal materials were collected through a literature review of legislation, legal doctrines, and relevant scholarly publications. The findings reveal that issuing a Regent Regulation without a preceding Regional Regulation may create formal legal defects concerning governmental authority (onbevoegd) and disrupt the hierarchy of legal norms. Since scholarship policies are strategic in nature and have implications for the Regional Revenue and Expenditure Budget (APBD), they should be regulated through a Regional Regulation enacted jointly by the regional head and the Regional People's Representative Council (DPRD). Although substantively consistent with the constitutional right to education and the National Education System Law, the policy remained formally vulnerable from a juridical perspective. The enactment of West Kotawaringin Regency Regional Regulation Number 4 of 2024 concerning Educational Scholarships represents legal rectification that strengthens policy legitimacy and reinforces vertical harmonization in accordance with the principles of lex superior derogat legi inferiori and legal certainty. The novelty of this study lies in examining the legality of a scholarship policy implemented through a Regent Regulation before the establishment of its primary normative foundation in a Regional Regulation.